PENGARUH SKEPTISISME PROFESIONAL, BATASAN WAKTU AUDIT, KODE ETIK PROFESI AKUNTAN PUBLIK DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT (Studi Kasus Pada Kantor Akuntan Publik di Tangerang dan Tangerang Selatan) - Sri Purwaningsih (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
This research aims to know the influence of skepticsm proffesionals, time limitation of audit, ethics of proffesional public accountant, competency auditor and audit quality. The object for this research is auditors who works at public accounting firm (KAP) in Tangerang and South Tangerang. The population research in this used 8 public accountant who worked on the public accounting firm (KAP) in South Tangerang and Tangerang City, with 80 respondents. The sample collection has been done by using convenience sampling method which is the sample collection technique is consideration of convenience. The multiple linear regressions analysis with SPSS version 20 and used as the analysis techniqueto test the hypothesis at 5% significance.The result of this research shows that either simultaneously, the variable of skepticsm profesional, time limitation of audit, ethics of profesional public accountant, and competency auditor influence audit quality. The result of this research shows that either partial, the variable of skepticsm profesional, ethics of profesional public accountant, and competency auditor influence audit quality. While the variable of time limitation of audit do not influence audit quality. It has been proven from the result of (F) simoultant test and the result of (t) partial shows significant point of four independent variables that supports the hipothesys. Therefore, the accepted assumption is, there is influence between skepticsm profesional, time limitation of audit, ethics of profesional public accountant, and competency auditor on audit quality at public accounting firm (KAP) in Tangerang and South Tangerang.